Research Methods in Psychology - Jhangiani, Rajiv S.; Chiang, I-Chant A. (Open textbook library., 2015)
The present adaptation constitutes the second Canadian edition and was co-authored by Rajiv S. Jhangiani (Kwantlen Polytechnic University) and I-Chant A. Chiang (Quest University Canada) and is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License. Revisions include the following: Chapter 1: Added a description of the “Many Labs Replication Project,” added a reference to the Neurobonkers website, and embedded videos about open access publishing, driver distraction, two types of empirical studies, and the use of evidence to evaluate the world around us.Chapter 2: Updated the exemplar study in the chapter overview, added relevant examples and descriptions of contemporary studies, provided a link to an interactive visualization for correlations, added a description of double-blind peer review, added a figure to illustrate a spurious correlation, and embedded videos about how to develop a good research topic, searching the PsycINFO database, using Google Scholar, and how to read an academic paper.Chapter 3: Added in LaCour ethical violation. Revised chapter headings and order to reflect TCPS-2 moral principles.Chapter 4: Added in difference between laws and effects and theoretical framework.Chapter 5: Added fuller descriptions of the levels of measurement, added a table to summarize the levels of measurement, added a fuller description of the MMPI, removed the discussion of the IAT, and added descriptions of concurrent, predictive, and convergent validity.Chapter 6: Added in construct validity, statistical validity, mundane realism, psychological realism, Latin Square Design. Updated references.Chapter 7: Added in mixed-design studies and fuller discussion of qualitative-quantitative debate.Chapter 8: Added an exercise to sketch the 8 possible results of a 2 x 2 factorial experiment.Chapter 9: Added information about Canadian Election Studies, more references, specific guidelines about order and open-ended questions, and rating scale. Updated online survey creation sites.Chapter 11: Updated examples and links to online resources.Chapter 13: Added discussion of p-curve and BASP announcement about banning p-values. Added a section that introduces the “replicability crisis” in psychology, along with discussions of questionable research practices, best practices in research design and data management, and the emergence of open science practices and Transparency and Openness Promotion guidelines. Glossary of key terms: Added. In addition, throughout the textbook, we revised the language to be more precise and to improve flow, added links to other chapters, added images, updated hyperlinks, corrected spelling and formatting errors, and changed references to reflect the contemporary Canadian context.